irpll Role of Patriarchy:With reference to English Victorian, Hindu Brahmin and Pashtun societies: Abida Ghilzai ,Dr. Faria Saeed Khan - jan, abdullah (JPL, 2023)
In the present study the role of Patriarchy with especial reference to English Victorian society depicted in Thomas Hardy‟s novel Tess of the D‟Urbervilles, Hindu Brahmin society portrayed in Bapsi Sidhwa‟s Water and Pashtun Society, has been analyzed. In this research paper the patterns of patriarchy, in the three societies; have been examined by applying qualitative textual analysis. Critics are of the view that the role of patriarchal characters in both novels and Pashtun society has been negative and dominant and religion has not been interpreted correctly by them. Patriarchy is one of the main issues of Radical feminism and this research paper has also been carried out with the viewpoint of radical feminist theory.